The Access to Faculty Initial Training and the Improvement of Teaching Quality - Urkidi Elorrieta, Pello; Losada Iglesias, Daniel; López Ramos, Victor; Yuste Tosina, Rocio (Revista Complutense de Educación, 2020)
The “European Higher Education Area” programme entails new bachelor´s degrees in Education in Spain. This article aims to analyse the initial training access of Pre-school and Primary Education teachers in the Spanish public universities. After carrying out a pilot study, data has been collected from the total of public centres through de database of the Ministry of Education of Spain, school years 2012-2013 and 2016-2017. The results obtained report a large variability in situations within each autonomous community, although at a state level it is confirmed that there is a progressive decrease in quota, a meaningful increase in cut-off marks, and a high motivation to take these degrees. In order to guarantee the quality of teaching, we conclude that it is necessary a better adjustment of the quota offer and a deep revision of teaching vectors.